Determinants of the growth of advertising agencies in the Republic of Serbia - Nuševa Daniela; Dakić Stojanka; Peštović Kristina; Vuković Bojana; Macura Nikola (Marketing (Beograd. 1991))
The subject of the research is the growth of advertising agencies in the Republic of Serbia in the period from 2007 to 2023. The paper aims to identify factors that significantly impact the growth of advertising agencies. Growth was analyzed based on the change in sales revenue between two consecutive periods. To examine which factors have a significant impact on the growth of sales revenue, the following independent variables were determined: indebtedness, return on assets, company size, time period before and during the crisis, income per employee. The research was conducted on a sample of 561 observations of indicators from the financial reports of advertising agencies with the application of panel regression analysis. The research results primarily indicate that advertising agencies on average achieve a positive growth in sales revenue, which indicates the stability of business over a long period of time. In the second part of the research, the results indicate that the return on assets and income per employee have a positive and significant impact on the growth of sales revenue. The company size variable has a negative impact on the growth of sales revenue. The results of the research indicate the profile of the decomposition of factors of growth of income from the sale of advertising agencies in the Republic of Serbia and provide an informative basis for making business decisions in the direction of further growth and development.